Capabilities of R&D: Literature Analysis - Asim, Zeeshan; Sorooshian, Shahryar; Muzamir, Hasan (IAEME Publication, 2018)
The establishment of new research idea as a path to narrow the literature gap and added studies in the field of Technology, Innovation, and Knowledge management capabilities and their interrelation impact on Research and development (R&D) has had become a significant challenge for R&D policy-makers. The study was a library search to highlight interrelationships of the R&D dominance (knowledge management, innovation management and technology management) and their subfields. The basic source material to construct academic yield was a one decade publications from 2006 to 2016.